Risk assessment of several hazards along railway network using AHP incorporated into GIS - Bennani, Nerdjes; Mezhoud, Samy (Technium Social Sciences Journal, 2023)
Located in northeastern Algeria, the region of Constantinois is undoubtedly among the regions most affected by various risks related to rail networks. These phenomena are one of the major development issues and a major and permanent threat to the population and existing facilities. The risks associated with rail field transport are associated with several parameters such as soft geological formations, steep slopes, hydrographic network, seismic frame and mainly problems linked to human accident, suicide and stones thrown. In this context, the objective of this paper is the identification of risk-prone areas in the rail network linking Constantine to Skikda (Algeria). This in order to highlight the relations that exist between several parameters: geological conditions, local topography, flow hydrographic network, vegetation...etc., and hazard treat on railway network such as settlement or landslide risk anthropic risk (risk of stone thrown and suicide accident). The methodology used is based on a GIS approach to identify areas susceptible, it is based on the interpretation of satellite map, topographic, geological and other data. The GIS project developed will allow to superimpose and analyze the effect of several factors on railway network integrity, these factors and their respective weights are then calibrated with statistical tool by adopting the method "Analytical Hierarchy Process" AHP. The resulting susceptibility maps distinguishes several degrees of susceptibility of areas that may be affected by collapse or accident problems of rail platforms. The comparison with the inventory map of several accidents that have already been recorded by railways services shows that the results obtained from the spatial modeling are very satisfactory.